What happens when tourism is turned off: Exploring the outcomes of the COVID-19 pandemic travel restrictions for Indigenous people in Rarotonga, The Cook Islands - Teaurere, Rerekura; De Waegh, Roxane (Frontiers in Sustainable Tourism, 2024)
The sea, sand and sun allure of the Cook Islands has seen tourism become the most significant driver of the country’s economic development. However, the increasing reliance on the tourism sector since the 1980s has created a mono-economy at the expense of diversification and alternative economic models. The COVID-19 pandemic emphasised the risks and consequences associated with an over- reliance on international tourism as the lockdown measures and international travel restrictions caused the sudden shutdown of international tourism, resulting in serious negative economic consequences for tourism-dependent communities. However, the pandemic also offered an opportunity for small island societies to reflect on pre-existing challenges associated with the tourism industry. Through qualitative semi-structured interviews with Indigenous Cook Islanders in Rarotonga, this study aimed to develop a deeper understanding of how the lived experiences of participants responding to the sudden collapse of tourism may have influenced how Indigenous Cook Islands peoples perceive the role of tourism in supporting the wellbeing of their small island nation. The presented study is the result of a collaborative research partnership between an Indigenous Pasifika scholar and non-Indigenous European scholar. While the research adopted a western methodology, the relationships developed between the researchers and participants were guided by the cultural values of reciprocity and respect, which are key principles underpinning Indigenous research in the Pacific. The findings revealed that participants adapted to the adverse impacts of COVID-19 through the revitalisation of their traditional socio-economies, the resurgence of customary practices, a strengthened connection to nature, and a renewed sense of community spirit and pride in cultural identity – all of which were perceived to positively impact their spiritual, social, cultural, environmental, physical and mental wellbeing. By demonstrating the positive adaptive responses of participants, this article aims to emphasise the non-economic dimensions of wellbeing that are critical to supporting the cultural values, social priorities, and the Indigenous ways of life that preceded the development of tourism. These findings can be used to inform and guide international development policy makers and tourism stakeholders who seek to reduce the adverse impacts of tourism on the wellbeing of Indigenous communities in the Pacific.